Impact of Information Technology (IT) on Education - Muh. Sifa; Titin Nurhidayati; M. Nafi'ur Rofiq (FALASIFA : Jurnal Studi Keislaman, 2023)
Since mid-March 2020, information and communication technology has played an important role in the world of education. After the emergence of a circular letter (SE) regarding the implementation of education during the Covid-19 emergency, the learning system at all levels of education switched to an online learning model. Online is the translation of the term online which means connected to the internet network. While online learning is learning that is carried out online using learning applications and social networks, so that information and communication technology, especially laptops and cellphones (HP) are the main facilities to support the ongoing teaching and learning process. This study tries to present an overview of the role, impact and problems of using information technology in the world of education along with solutions to these problems. This study uses a descriptive qualitative approach whose purpose is to reveal facts, phenomena, variables contained in the research object. The source of the data for this study was from the author's observations at several schools and interviews with several teachers and took data from journals or literature from the internet related to the above theme. The results of this study are: 1) The role of information technology in the world of education, 2) The impact of information technology in the world of education, 3) The problems of using information technology in the world of education and their solutions.